2015
DOI: 10.1364/optica.2.000563
|View full text |Cite
|
Sign up to set email alerts
|

Gating attosecond pulses in a noncollinear geometry

Abstract: International audienceThe efficient generation of isolated attosecond pulses (IAPs), giving access to ultrafast electron dynamics in various systems, is a key challenge in attosecond science. IAPs can be produced by confining the extreme ultraviolet emission generated by an intense laser pulse to a single field half-cycle or, as shown recently, by employing angular streaking methods. Here, we experimentally demonstrate the angular streaking of attosecond pulse trains in a noncollinear geometry, leading to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Another possibility to achieve WFR is non-collinear optical gating (NOG). Here, the idea is to cross two equally strong delayed pulses [61,62]. Then, the wave front orientation will change continuously from the direction of the first pulse to the one of the second pulse, leading to an attosecond lighthouse effect as in the case of the spatially chirped driving pulse.…”
Section: Identification Of Promising Gating Methods For Cavity-enhancmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility to achieve WFR is non-collinear optical gating (NOG). Here, the idea is to cross two equally strong delayed pulses [61,62]. Then, the wave front orientation will change continuously from the direction of the first pulse to the one of the second pulse, leading to an attosecond lighthouse effect as in the case of the spatially chirped driving pulse.…”
Section: Identification Of Promising Gating Methods For Cavity-enhancmentioning
confidence: 99%
“…Production of IAPs by NOG was only experimentally demonstrated with sub-two-cycle pulses [62]. However, [61] predicts that separation of an IAP is still possible with 10 fs pulses at 800 nm, which corresponds to 3.75 cycles, assuming a harmonic beamlet divergence angle of Q 0.1 0 , with Q 0 denoting the divergence angle of the driving beam.…”
Section: Identification Of Promising Gating Methods For Cavity-enhancmentioning
confidence: 99%
“…The ability to measure and quantify the achieved degree of compression is therefore paramount to identify the main characteristics of the output pulse and to further optimize its compression. Both spectral phase oscillations and the overall spectral phase of a pulse can be visualized in a very straightforward way using the dispersion-scan (d-scan) [41] technique, which has been extensively used in the last years to characterize many state-of-the-art few-cycle pulse sources around the world and is enabling new and very promising applications [6,[38][39][40]42]. D-scan is a recent approach for the simultaneous measurement and compression of femtosecond laser pulses.…”
mentioning
confidence: 99%
“…But, the single attosecond pulses (SAPs) is much more favorable to the time-resolved dynamics measurement. Thus, several approaches have been proposed to obtain the SAPs, including the ionization and the polarization gating methods [12][13][14][15][16][17][18][19][20], the attosecond lighthouse [21][22][23] and the mix-color field method [24][25][26][27][28][29][30][31][32] etc. Recently, beyond the SAEA, Zhao's group [33,34], Feng et al [35] and Koval et al [36] investigated the HHG They found that due to the multi-electron effect, the harmonic cutoff can be further extended but with a very lower harmonic intensities in the extended region.…”
Section: Introductionmentioning
confidence: 99%